Descemet Endothelial Thickness Comparison Trial 1 (DETECT 1): outcome masked, placebo-controlled trial comparing two types of corneal transplant surgeries and effect of rho kinase inhibitors on endothelial cell loss protocol - Thomas M Lietman; Jennifer Rose-Nussbaumer; Bennie H Jeng; Benjamin F Arnold; Winston Chamberlain; Charles C Lin; Jennifer Y Li; William Gensheimer; Jameson Clover; Nicole Varnado; Sarah Abdelrahman (BMJ Open Ophthalmology)
Background It remains uncertain which endothelial keratoplasty (EK) technique yields the best outcomes while maintaining safety, particularly in eyes with coexisting ocular conditions. Moreover, the impact of endothelial cell loss (ECL) on long-term graft survival requires further investigation. Adjuvant ripasudil, a rho kinase inhibitor, may address the challenge of ECL in corneal transplantation. This paper presents the protocol for the Descemet Endothelial Thickness Comparison Trial 1 (DETECT 1), a multicentre, outcome-masked, randomised, placebo-controlled, four-arm clinical trial.Methods A total of 160 eligible patients with endothelial dysfunction will be enrolled from five participating sites in the USA. The patients will be randomly assigned in a 2×2 factorial design to one of the following treatment groups: group 1—ultrathin Descemet stripping endothelial keratoplasty (UT-DSAEK) plus topical ripasudil 0.4%; group 2—UT-DSAEK plus topical placebo; group 3—Descemet membrane endothelial keratoplasty (DMEK) plus topical ripasudil 0.4% and group 4—DMEK plus topical placebo. Primary outcomes include the best spectacle-corrected visual acuity at 12 months and ECL at 12 months. Secondary outcomes include visual acuity at different time points, vision-related quality of life, endothelial cell morphology and cost-effectiveness.Results The study outcomes will be analysed using mixed effects linear regression models, taking into account the treatment arms and relevant covariates. Adverse events, including rebubble procedures, graft failure and graft rejection, will be documented and analysed using appropriate statistical methods.Conclusion DETECT I aims to provide evidence on the comparative effectiveness of UT-DSAEK and DMEK, as well as the potential benefits of adjuvant topical ripasudil in reducing ECL. The results of this trial will contribute to optimising corneal transplantation techniques and improving long-term graft survival, while also exploring the cost-effectiveness of these interventions. Dissemination of findings through peer-reviewed publications and national/international meetings will facilitate knowledge translation and guide clinical practice in the field of corneal transplantation.Ethics and dissemination A data and safety monitoring committee (DSMC) has been empaneled by the NEI.All study protocols will be subject to review and approval by WCG IRB as the single IRB of record.This study will comply with the National Institute of Health (NIH) Data Sharing Policy and Policy on the Dissemination of NIH-Funded Clinical Trial Information and the Clinical Trials Registration and Results Information Submission rule. Data from the trial will be made available on reasonable request.